Pengaruh Biaya Produksi Dan Biaya Operasional Terhadap Laba Bersih PT. Mayora Indah Tbk Periode 2012-2021 - Tania Eka Putri; Endang Mahpudin (Peneliti.net, 2023)
All businesses always aim to increase their profits. The profits obtained can be maximized by emphasizing and controlling the costs to be acquired by the company. The desire of this analysis is to ensure net income PT. Mayora Indah Tbk will be affected by production costs and operating costs. from 2012 to 2021. The approach worn in this analysis is quantitative, with the association problem formulated as a causal relationship. The data source for this research is secondary data in the form of financial statements for the period 2012-2021 of PT. Mayora Indah, Tbk. Based on the conclusion of the analysis, it appearance that there are those that admit a significant effect on net income, and there are also operational costs that have a significant effect on net income. Also, production costs and operating costs together or simultaneously appearance a significant impact at net income